Identification and quantification of the main organic components in artisanal apple vinegars from Iraq Kurdistan region by 1H NMR spectroscopy - Lana H. Chawishli (Zanco Journal of Pure and Applied Sciences, 2024)
The proton NMR spectra of apple vinegar samples obtained from the farms of Kurdistan region-Iraq, have been thoroughly examined and reported. Many organic molecules from various classes were assigned, including organic acids, alcohols, volatile compounds, and amino acids. Without extraction or pre-concentration processes, the possibility of quantifying the compounds that were present in the whole vinegar sample was also investigated. The results showed that 1H NMR with water suppression allows a quick simultaneous determination of acetic, formic, lactic, malic, succinic, tartaric acids, ethanol, methanol, acetoin, 2,3-butanediol, glucose and fructose, by using dimethyl sulfone (DMSO2) or potassium hydrogen phthalate (KHP) as internal standards. The 1H NMR method was applied to differentiation of the various samples of apple vinegar.